1991
DOI: 10.1210/endo-128-6-2731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Regulation of High Affinity Calcitonin Gene-Related Peptide Receptors in Cultured Neonatal Rat Cardiac Myocytes*

Abstract: Previous studies have shown that stimulation of cultured beating cardiac myocytes with calcitonin gene-related peptide (CGRP) produces increased beating frequency, increased cellular cAMP concentration, and a homologous desensitization of the cAMP-elevating action of CGRP. In the present study, the characteristics and regulation of [125I]CGRP binding sites in cultured cardiac myocytes were investigated. Binding of [125I] CGRP to membranes prepared from these cells was selective, saturable, and of high affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The effect of GTP-)I-S and the lack of binding inhibition by unrelated peptides further emphasizes the binding specificity in rat lung. Our results, therefore, provide evidence that 125 I-hCGRP binding sites are present in the rat lung and are regulated by guanine nucleotides, which is in agreement with similar behaviour seen with CGRP binding sites in other tissues [14,15,17].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The effect of GTP-)I-S and the lack of binding inhibition by unrelated peptides further emphasizes the binding specificity in rat lung. Our results, therefore, provide evidence that 125 I-hCGRP binding sites are present in the rat lung and are regulated by guanine nucleotides, which is in agreement with similar behaviour seen with CGRP binding sites in other tissues [14,15,17].…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that 125 I-hCGRP binding sites may be sensitive to structural changes in the hCGRP molecule, in that removal or modification of the N-terminal caused a reduction in inhibitory potency, as seen with a-hCGRP and [Cys(ACM) 2,7 ]hCGRP compared to hCGRP. Similar observations have been made previously in rat brain and cultured neonatal rat cardiac myocytes [14,15]. However, in membrane preparations of rat and guinea-pig tissues, a-hCGRP has been shown to have a greater inhibitory potency relative to hCGRP for 125 I-hCGRP binding sites [8], suggesting that there may be regional or species differences in the binding affinity of 125 I-hCGRP binding sites.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The relative potency of human amylin to induce cAMP production by KS-4 cells correlated with the binding affinity of this peptide for CGRP receptors in the rat brain. Chatterjee et al (1991) characterized high affinity receptors for CGRP in cultured rat cardiac myocytes. Amylin displaced the CGRP binding, but its affinity was much weaker than that of CGRP (Chatterjee et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al (1991) characterized high affinity receptors for CGRP in cultured rat cardiac myocytes. Amylin displaced the CGRP binding, but its affinity was much weaker than that of CGRP (Chatterjee et al, 1991). Zhu et al (1991) also reported that amylin increased cAMP production by L6 myocytes via CGRP receptors.…”
Section: Discussionmentioning
confidence: 99%